1998
DOI: 10.1002/(sici)1099-1263(1998090)18:5<331::aid-jat517>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chelating agents on the toxicity and distribution of beryllium in rats

Abstract: The effect of two new chelating agents—Tiron (4,5‐dihydroxy‐1,3‐benzene disulphonic acid disodium salt) and succinic acid—on the mobilization of beryllium was studied. Animals were exposed to beryllium nitrate (1 mg kg−1 i.p.) daily for 21 days. Administration of beryllium nitrate showed a marked decrease in haemoglobin percentage, blood sugar, serum alkaline phosphatase and serum protein and a significant increase in the activity of transaminases. Tissue protein and glycogen contents and the activity of alkal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Mathur et al (1993) have investigated the efficacy of three polyaminocarboxylic acids -ethylenediaminetetraacetic acid (CaNa 2 EDTA), diethylenetriamine pentaacetic acid (CaNa 3 DTPA) and N-(2-hydroxyethyl)-ethylenetriaminetriacetic acid (HEDTA) -against beryllium toxicity. Preliminary studies confirm the efficacy of Tiron, significantly over the other chelators Shukla et al 1998). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathur et al (1993) have investigated the efficacy of three polyaminocarboxylic acids -ethylenediaminetetraacetic acid (CaNa 2 EDTA), diethylenetriamine pentaacetic acid (CaNa 3 DTPA) and N-(2-hydroxyethyl)-ethylenetriaminetriacetic acid (HEDTA) -against beryllium toxicity. Preliminary studies confirm the efficacy of Tiron, significantly over the other chelators Shukla et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, , and Shukla et al (1998) have reported the efficacy of Tiron (4,5-dihydroxybenzene-1,3-disulfonic acid disodium salt) against beryllium intoxication in preliminary studies, so the present study was planned to investigate the efficacy of Tiron on pregnant female rats and developing fetuses.…”
Section: Introductionmentioning
confidence: 99%
“…Chelators are common forms of therapy used to eliminate beryllium from the body and reduce its toxic effects. Relevant chelators include 4,-dihydroxy-1,3-benzene disulphonic acid disodium salt (Tiron) and D-penicillamine (DPA), which proved to be effective when tested in animals [35][36][37]. Also, the chelator meso-2,3-dimercaptosuccinic acid (DMSA) was used in a case study to successfully save a child suffering from heavy metal poisoning [38].…”
Section: Berylliummentioning
confidence: 99%
“…In this paper, we looked into the therapeutic potential of three organic ligands, nitrilotripropionic acid (NTP), nitrilotriacetic acid (NTA) and 4,5-dihydroxy-1,3-benzenedisulfonic acid (tiron) using an adapted version of the human BeLPT performed on mouse splenocytes, hereafter named the splenocyte proliferation test (SPT). These chelators were selected from an in-depth literature search on appropriate beryllium complexing agents (Price and Joshi, 1984;Scarrow et al, 1985;Clevette et al, 1989;Mathur et al, 1993;Chinea et al, 1995;Shukla et al, 1998;Cecconi et al, 2002;Sharma et al, 2002;Kontoghiorghes, 1995). Based on coordination chemistry and basicity of the donor groups, we selected NTP given that the beryllium cation in the [Be(NTP)] − complex lies at the center of a slightly distorted tetrahedron towards C 3ν symmetry with a longer Be-N bond and three equal Be-O bonds.…”
Section: Introductionmentioning
confidence: 99%
“…NTA belongs to the same family of amino carboxylic acids as NTP and was selected to evaluate the potential preference of beryllium towards ligands that form five-membered ring chelates (acetic groups) or six-membered ring chelates (proprionic groups) (Chinea et al, 1995). From immunotoxicological studies, tiron was also chosen because it has been shown to reduce berylliuminduced hematological alterations and histopathological lesions in the liver (Shukla et al, 1998). Tiron was also shown to mobilize beryllium and restore the altered biochemical parameters in different rat tissues and organs Nirala et al, 2007).…”
Section: Introductionmentioning
confidence: 99%